PHQ-9 and SNOT-22: Elucidating the Prevalence of Depression in Chronic Rhinosinusitis. (January 2020) - Vandelaar, Laura J.; Jiang, Zi Yang; Saini, Alok; Yao, William C.; Luong, Amber U.; Citardi, Martin J.
Objective: Chronic rhinosinusitis (CRS) has been associated with comorbid depression, yet the prevalence of depression among all patients with CRS is not well described. The Patient Health Questionnaire–9 (PHQ-9), a validated instrument for diagnosing depression, has been used to assess depression in a variety of clinical settings. PHQ-9 scores ≥10 are the threshold for a depression diagnosis. The purpose of this study was to assess the prevalence of depression in a rhinology practice and compare the PHQ-9 with the 22-item Sinonasal Outcome Test (SNOT-22). Study Design: Retrospective chart review. Setting: Tertiary rhinology practice. Subjects and Methods: During the 2-month period ending April 30, 2018, all rhinology patients were asked to complete the PHQ-9 and SNOT-22. Results: Among 216 patients, 46 (21.3%) had a self-reported history of depression, and 39 (18.1%) had a PHQ-9 score ≥10. Of the 39 patients screening positive for depression, 18 (41.9%) had no history of depression. Comparison of PHQ-9 with overall SNOT-22 score had a Pearson's coefficient of 0.632 ( P < .005). Logistic regression showed that the highest 2 quintiles of SNOT-22 scores had an odds ratio of 60.6 (95% CI, 9.7-378.3) for a positive depression screen (PHQ-9 score ≥10). Conclusion: Depression rates (estimated by PHQ-9 responses) among rhinology patients are similar to chronic disease populations; depression may be underdiagnosed in rhinology patients. Higher SNOT-22 scores were associated with higher PHQ-9 scores. Further studies are warranted to understand the impact of comorbid conditions of depression and CRS in patient quality of life.